Thermodynamic Analysis of Sub and Supercritical Water Gasification of Aqueous Fraction of Hydrothermal Liquefaction of Biomass for Production of Hydrogen Rich Bio-Gas - Kumar, Rakesh; Raha, Sasanka; S. Apegaonkar, Supriya; Bhujade, Ramesh (Recent Innovations in Chemical Engineering, 2016)
Background: The Hydrothermal liquefaction (HTL) of the biomass generates two phases, namely, liquid bio crude & an aqueous phase containing soluble hydrocarbons. Hydrothermal gasification converts aqueous hydrocarbons into fuel gas containing mainly CH4,H2 and CO2. Objective: Objective of the present study is to carry out thermodynamic analysis of sub and supercritical water gasification of aqueous fraction of HTL for hydrogen rich bio-gas production. Method: In this study, equilibrium composition calculations for sub and supercritical water gasification product performed using Gibbs method for aqueous HTL fraction & its constituent components. Results: Thermodynamic model was validated with experimental data at different operating conditions. Sensitivity study of critical process parameters (for individual constituents components of HTL aqueous fraction and their multicomponent mixture) conducted over broad range, namely, temperature (300-1000°C), pressure (190-340 bar) and feed concentration (1-30 wt%) to identify optimum process condition. Conclusions: Increase in reaction temperature shows the positive effect on hydrogen mole fraction in product gas mixture. However, increase in pressure leads to decrease in hydrogen mole fraction in product. Maximum hydrogen concentration in the range of 0.60-0.75 mole fraction (depending upon selected composition of organics in multicomponent aqueous fraction) was observed in the bio-gas at temperature of 705°C. Lower feedstock concentration of aqueous HTL organics is observed to lead to high hydrogen production.
Keywords: Hydrothermal liquefaction